ANALISIS EFEKTIVITAS PENERIMAAN RETRIBUSI PENGUJIAN KENDARAAN BERMOTOR PADA DINAS PERHUBUNGAN KABUPATEN ENDE - Gena, Sofia; Londa, Yulita; Thalib, Sabra B Wahab (Program Studi Akuntansi Universitas Flores, 2023)
The aims of this study are, (1) to determine the effectiveness of receiving motorized vehicle testing fees (2) to determine the factors that influence the effectiveness of receiving motorized vehicle testing fees. The type of research used in this research is descriptive. Data obtained by means of observation, interviews, documentation. The data analysis technique used is quantitative descriptive, namely calculating the level of effectiveness of acceptance of motorized vehicle testing fees in Ende Regency from 2019-2021. The results of this study show that the effectiveness of receiving motor vehicle testing fees in Ende Regency in 2019 was 77.33%; in 2020 at 26.13%; and in 2021 it will be 4.28. Thus the effectiveness of receiving motor vehicle testing fees in Ende Regency, during 2019-2021 is not effective because the effectiveness rate is less than 100%. This shows that the performance of the Regional Government of Ende Regency, especially the Department of Transportation during 2019-2021, was not good in carrying out their duties, while the factors that affect the effectiveness of receiving motorized vehicle testing fees are, (10) lack of socialization of government officials from the Department of Transportation to the public about the importance of vehicle testing motorized vehicles; (2) weaknesses in supervision from government officials in ordering vehicles; (3) human resources in terms of expert testing staff; (4) lack of supporting facilities; (5) lack of public awareness and knowledge; (5) the existence of a covid-19 outbreak 19 which requires people not to gather.